Antimicrobial nanocapsules: from new solvent-free process to in vitro efficiency - Steelandt J (Dove Medical Press, 2014)
Julie Steelandt,1 Damien Salmon,1,2 Elodie Gilbert,1 Eyad Almouazen,3 François NR Renaud,4 Laurène Roussel,1 Marek Haftek,5 Fabrice Pirot1,2 1University Claude Bernard Lyon 1, Faculty of Pharmacy, Fundamental, Clinical and Therapeutic Aspects of Skin Barrier Function, FRIPharm, Laboratoire de Pharmacie Galénique Industrielle, 2Hospital Pharmacy, FRIPharm, Hospital Edouard Herriot, Hospices Civils de Lyon, 3Laboratoire d’Automatique et de Génie des Procédés, University Claude Bernard Lyon 1, 4University Claude Bernard Lyon 1, UMR CNRS 5510/MATEIS, 5University Claude Bernard Lyon 1, Faculty of Pharmacy, Fundamental, Clinical and Therapeutic Aspects of Skin Barrier Function, FRIPharm, Laboratoire de Dermatologie, Lyon, France Abstract: Skin and mucosal infections constitute recurrent pathologies resulting from either inappropriate antiseptic procedures or a lack of efficacy of antimicrobial products. In this field, nanomaterials offer interesting antimicrobial properties (eg, long-lasting activity; intracellular and tissular penetration) as compared to conventional products. The aim of this work was to produce, by a new solvent-free process, a stable and easily freeze-dryable chlorhexidine-loaded polymeric nanocapsule (CHX-NC) suspension, and then to assess the antimicrobial properties of nanomaterials. The relevance of the process and the physicochemical properties of the CHX-NCs were examined by the assessment of encapsulation efficiency, stability of the nanomaterial suspension after 1 month of storage, and by analysis of granulometry and surface electric charge of nanocapsules. In vitro antimicrobial activities of the CHX-NCs and chlorhexidine digluconate solution were compared by measuring the inhibition diameters of two bacterial strains (Escherichia coli and Staphylococcus aureus) and one fungal strain (Candida albicans) cultured onto appropriate media. Based on the findings of this study, we report a new solvent-free process for the production of nanomaterials exhibiting antimicrobial activity, suitable stability, and easily incorporable as a new ingredient in various pharmaceutical products. Keywords: nanomaterial, nanocapsules, antiseptic, chlorhexidine, solvent-free process